Serum-derived piR-hsa-164586 of extracellular vesicles as a novel biomarker for early diagnosis of non-small cell lung cancer - Li, Yanli; Dong, Yanhan; Zhao, Shupeng; Gao, Jinning; Hao, Xiaodan; Wang, Zibo; Li, Meng; Wang, Mengyuan; Liu, Yiming; Yu, Xiaoling; Xu, Wenhua (Frontiers in Oncology, 2022)
Non-small cell lung cancer（NSCLC）is a major cause of death among malignant tumors.In order to diagnose early NSCLC patients,we investigated serum-derived exosomal PIWI interacting RNA（piRNA）to filter diagnostic biomarkers for NSCLC. High throughput sequencing was firstly applied to recognize candidate piRNA as diagnostic biomarkers from cancerous tissues and adjacent noncancerous tissues in patients with NSCLC. These screened piRNAs were further validated in 115cases(including 95 cases in stageⅠ) of patients and 47 cases of healthy persons by quantitative Real-time PCR (qRT-PCR).Based on the results,piR-hsa-164586 was significantly up-regulated compared with paracarcinoma tissues and exosomes from serum samples with healthy persons.Moreover,the area under the curve(AUC) value of piR-hsa-164586 achieved 0.623 and 0.624 individually to distinguish patients with all stages or stageⅠof NSCLC from healthy.Compared with the cytokeratin-19- fragment(CYFRA21-1), the diagnostic performance of piR-hsa-164586 has been greatly improved.Additionly,piR-hs-164586 was also closely related to the clinical characteristics of patients with NSCLC.Its expression was link to the age and TNM stage of patients with NSCLC,indicating that they can be served as effective and promising biomarkers for early diagnosis of patients with NSCLC.